Realistic modeling of power lines for transient electromagnetic interference studies - Britto, Amauri Gutierrez Martins (2020)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2020.